GOOD AND BAD EDUCATIONAL ENVIRONMENT IN ISLAM - Dalmi Iskandar Sultani; Cita Ayni Putri Silalahi; Sujarwo; Azrai Harahap; Hafizah Zulkifli; Azzahara Kusuma Dewi; Khotimatunnisa Sinaga (International Review of Practical Innovation, Technology and Green Energy (IRPITAGE), 2025)
This activity is called International Visiting Lecture, Community Service and Knowledge Transfer Programme. Using the method of presentation of ideas/technologies and discussions. The results of activities, percentages and discussions about good and bad educational environments, namely the educational environment of families, schools, communities and mosques. If the environment is maintained and maintained and carried out various programs and activities that are useful or well functioned, it will be a good environment. However, if the environment is not maintained, maintained, and functioned as it should, it will become a bad environment. A good environment is a good environment that is beneficial for children's life and growth, a bad environment is one that has an impact on the bad or damaged growth and development of children.